2018
DOI: 10.1111/pde.13533
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic annular erythema treated with dupilumab

Abstract: Eosinophilic annular erythema is a rare, benign, recurrent condition characterized by annular skin lesions, tissue eosinophilia, and resistance to a variety of treatments. There are fewer than 30 cases reported in the English literature, 7 of which are in children. We present a case of recurrent eosinophilic annular erythema in an adolescent that was successfully treated with dupilumab, an interleukin-4 receptor alpha antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 4 publications
0
28
0
4
Order By: Relevance
“…Suplatast tosilate, an anti-allergic medication that suppresses the production of IgE and synthesis of IL-4 and IL-5, was administered to one patient with EAE, resulting in complete resolution of the lesions within 2 weeks [16]. Dupilumab, an IL-4 receptor alpha antagonist, was also successfully used in a 14-year-old African-American girl with EAE [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suplatast tosilate, an anti-allergic medication that suppresses the production of IgE and synthesis of IL-4 and IL-5, was administered to one patient with EAE, resulting in complete resolution of the lesions within 2 weeks [16]. Dupilumab, an IL-4 receptor alpha antagonist, was also successfully used in a 14-year-old African-American girl with EAE [17].…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature revealed that only about 40 cases of EAE in adults and fewer than 10 cases in children have been reported to date. Among adult patients, a slight female preponderance has been noted (female:male ratio 1.14:1), and age at onset varies from 20 to 85 years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, patients with both atopic dermatitis and alopecia areata treated with dupilumab have repeatedly demonstrated hair regrowth (103105). Furthermore, some isolated cases were published with beneficial results in bullous pemphigoid (106), eosinophilic annular erythema (107), and papuloerythroderma of Ofuji (108).…”
Section: Discussionmentioning
confidence: 99%
“…Es ist charakterisiert durch rezidivierende, anuläre, erytheamtös‐ödematöse, pruritische Erytheme mit Gewebseosinophilie. Im Gegensatz zum Well's Syndrom zeigen sich meist weder eine periphere Eosinophilie noch ”flame figures” oder granulomatöse Strukturen in der Histologie[1]. Aktuelle Therapieoptionen beinhalten systemische Steroide, Dapson und Hydroxychlorquin, wobei das EAE sich häufig therapierefraktär zeigt und zu Rezidiven neigt [2–4].…”
Section: Kommentarunclassified